Listening to music at home and at school - Boal-Palheiros, G. (2018)
This study investigated the differences between the functions of music listening at home and at school, and the potential effects of age and nationality on these differences. 120 participants completed an individual structured interview schedule, which consisted of ten open-ended questions. These covered the role of music listening in young people's leisure interests as a whole, and more speci®c aspects of listening at home and at school. Sixty participants were from schools in the UK, and sixty from schools in Portugal: within each nationality group, thirty were aged 9±10 years and thirty aged 13±14 years. The ®ndings showed that music listening was an important leisure activity, especially for the older children, and that most children showed moderate positive attitudes towards school music. Home music listening and school music ful®lled different functions: participants reported that home listening was linked with enjoyment, emotional mood and social relationships, whereas school music was associated with motivation for learning and being active, and particular lesson content. There were few clear-cut national differences, and music was generally undervalued in both countries.